(untitled) (Iter, 2022)
According to Aristotle in his Politics, food provided by nature determines not only how animals, but also how humans, live. However, human beings have been created as nature’s objective; humans can control and transform nature for their own benefit through technique, as far as nature allows them to. In the realm of knowledge and through experience, nature conditions science as much as technique does (Metaphysics). From the political perspective, it is nature what determines who are free and capable for civil government, and the primal methods of association: family, village. Aristotle’s approach on the relationship between man and nature has been accepted for centuries, in spite of the fact that it seems out of place in our modern world. This can be attested through approaches by authors such as José Ortega y Gasset or Hannah Arendt, for instance.